A review of the port carbon emission sources and related emission reduction technical measures. (1st March 2023) - Wang, Bei; Liu, Qing; Wang, Lei; Chen, Yongjun; Wang, Jisheng
Abstract: Shipping emission reduction is one of the most critical issues in the transportation industry and world emission reduction research. Ports, as important hubs and sources of emissions have also received much attention. This paper investigated the development process of port emission reduction from earlier 'environmental factors and energy scheduling' to 'low-carbon and green ports' by conducting a systematic review and Citespace visual analysis. It can be also concluded that the policy has a great impact on the development of this research field. Meanwhile, this review found that among the emission reduction measures for ships in port, the average percentage of the energy measures potential is 25%–70%. The range of optimization operation measures is 30%–50%. There is a gap between the two measures. According to the diverse emission sources in the port, there is no significant difference (20%–60%) for the potential of measures application in land area. Therefore, before setting the reduction targets, ports need to know their emission level and establish emission inventories, as well as consider external factors (policy, economy, technology, etc.). Overall, port energy measures are the key points to achieving low and zero carbon targets. In the future, by addressing technical bottlenecks in energy use (such as hydrogen storage and maintenance), ports and ships will be able to further reduce their dependence on fossil fuels and increase their potential to reduce emissions. This paper aims to systematically review and explore the effects (experiences) and problems (challenges) of the abatement measures taken by different ports, to help low-abatement capacity ports to learn and find the measures that suit the emission reduction development most. For the choice of future energy, the port needs to analyze the corresponding policy factors and improve the abatement capacity through the integration of multiple measures, to understand the 'zero carbon goal' as soon as possible and make contributions to the environmental protection and ecological development of the region and world. Graphical abstract: The Image 1 shows the discussion and analysis of port and ship in port emission reduction measures in the review. It screened and included the relevant research literatures of CNKI and Web of Science through Systematic review, as well as, use Citespace for visual analysis. In terms of Potential of Emission Reduction Measures for Ships: Energy measures can make 25% 70% and the Optimized Operational Measures can make 30% 50%. In terms of Potential of Emission Reduction Measures for Ports: the Emission Potential of each Emission Measure is similar. The range is 20% 60%. There are two existing constraints for Emission Reduction Measures. The port internal factors include technology maturity and investment cost related to each measures. The port external factors include policy, economy, etc. In summary, despite the differences in functions, scales, types, and management modes, all these measures can influence port emission reduction. These measures can reduce emissions while bringing economic benefits. The energy measures will further help the port to free itself from dependence on fossil fuels and achieve the goal of 'zero carbon' as soon as possible as the technology becomes more mature, and the cost is reduced and the external conditions of the port and the ships in the port are improved. Image 1 Highlights: Citespace and systematic review facilitate collecting and summarizing the literature. Energy measures are the key guarantee for port emission reduction. Emission inventories for ports should be formulated at different development stages. Port emission reduction researches need to strengthen cooperation in all aspects. More research cases improve emission reduction policy formulation and implementation.